Success factors of Smart Cities Initiatives - Manu, Yaw Agyei (Univerzita Pardubice, 2019)
The aim of this paper was to find out the Smart city in the world and that of Europe, their critical success factors that help them in smartness. Things the cities did in the initiative that they have in common. There was some technology and models that each city used, they all emphasis in some key dimension that help them achieve their goal.
Faktory úspěchu iniciativ inteligentních měst
Keywords: inteligentní města; kritické faktory úspěchu; Smart cities; critical success factors